A SMALL-SCALE PARA RUBBER SHEET SMOKING AND DRYING SYSTEM USING SOLAR ENERGY COMBINED WITH BIOMASS STOVE - Netkham, Hathaichanok; Chindaraksa, Sirinuch Chindaraksa (Life Sciences and Environment Journal, 2017)
A small-scale para rubber sheet smoking and drying system was developed by using solar energy combined with biomass stove. In this study, the greenhouse dryer (dimensions: 2.50 m in width, 2.50 m in height and × 2.50 m in length) using transparent polycarbonate sheet-covered greenhouse solar dryer and biomass stove used as a auxiliary heat source (dimensions: 0.75m in width, 0.80m in length and 0.80m in height). Gas to Gas heat exchanger with total area is about 2.5 m2. The capacity of dryer is 20 sheets of para rubber (weight, 24 kilograms) per time at initial moisture content of 50 %db and the final moisture content of 3 %db Experimental was divided into 3 factors: 1) drying by solar energy only 2) drying by solar energy throughout the day and biomass furnace at night. 3) drying by combining solar energy and biomass furnace throughout the experiment. Factor 3, the temperature inside the drying chamber is controlled by connecting the hot-air blower at 55–60°C for 60 hours. The drying energy consumption is 1,173 MJ/kg or equivalent to 168 MJ/kg H2Oevap.The payback period was considered in drying system using solar energy combined with biomass stove showed as follows: 1) the lifetime of dryer is 5 years of 80 batches of para rubber during each year 2) the return on investment is 128,920 baht per year, the total investment cost is about 459,439 baht and the payback period is 3.56 years.